Supporting student learning through the use of a sequential case study workbook: An inductive content analysis of student feedback. (May 2020) - Christensen, Martin; Lynch, Joan
Abstract: Background: The use of workbooks to support nursing student learning are not new. Used in a variety of guises and differing delivery formats from printed to electronic, enables nursing students to engage in specific complex patient conditions with the view to enhancing and support learning. However, evaluating the effectiveness of the workbook itself is often overlooked, instead value is expressed in academic success. Aim: The aim of this study was to evaluate the effectiveness of a sequential based workbook to support student learning. Method: Inductive content analysis was used to identify text patterns from end of semester student feedback. In all, three generic themes were identified – Usability, Knowledge and Content and Workload to create a main theme – The Living Workbook. Results: On the whole students found the workbook a user-friendly medium to support learning and importantly being able to apply the knowledge into the practice setting. There were a number of students who disliked the workbook because of the complexity of the case studies being presented and for being content heavy. Conclusions: Despite the challenges of passing the unit, the use of a sequential workbook to enhance the reality of providing nursing care to complex and challenging patient conditions was seen favourably. Highlights: A sequentially based workbook can prove beneficial in supporting students learning and application; Most students found the workbook to be good revision aide for exams; Some students saw the workbook supporting clinical placement rotations; Most students found the realism particularly useful in applying nursing knowledge and skills more appropriately.